2018 saw a sharp increase in air crash deaths: visualizing and evaluating risk. Issue 1 (10th March 2021) - Anderson, Joe; Williams, Susan K.
Abstract : Theoretical basis: Risk literacy matters for business students. A significant aspect of decision-making is accurately evaluating the risks involved in a decision. Research shows that many people are challenged to understand simple, health-relevant risk rates and probabilities. It also shows that many people are functionally innumerate, even educated people like doctors. While there is much academic work in health aimed at understanding how to communicate health risks to patients, an important personal area for business students, there are many industries and organizations where understanding risk is important for business students' careers. This case provides opportunities for business students to practice these skills. Research methodology: This is a secondary-data, compact case. The impetus for the case was a blog and the data gathered is primarily from Aviation Safety Net, Worldbank, Airlines.org, International Air Transport Association and Statista.com . Case overview/synopsis: Coming across a blog headline, a professor is dismayed at the message: 2018 saw a sharp increase in air crash deaths. Questioning that the headline is appropriate and that the number of fatalities is an appropriate measure, the professor sets out to analyze airline safety data. Complexity academic level: This case is intended for undergraduate or graduate students in an introductory business analytics course. The focus is on using and communicating risk rates and visualization.